Analisis Pengaruh Meningkatnya Jumlah Kemiskinan di Jakarta Dalam 20 Tahun Terakhir Terhadap Jumlah Kriminalitas di Wilayah Hukum Polda Metro Jaya - Stefanus Timonora Wahyu Ariyanto; Awaluddin Tjalla; mahdiyah mahdiyah (Jurnal Litbang Polri, 2023)
The purpose of this study is to provide an overview of the increasing number of poverty in Jakarta in the last 20 years and its effect on the number of crimes in the jurisdiction of polda Metro Jaya. The method used is a quantitative method by taking data from the Central Statistics Agency (BPS) and analyzed with the help of the SPSS version 25 application and using regression techniques to see the influences that arise. From the results of the Hypothesis Test, it was found that based on the significance value from the Coefficients table, a significance value of 0.000 was obtained, which means < 0.05, in other words, reject H0 so that it can be concluded that the poverty variabel (X) affects the crime variabel (Y). Based on the value of t, a calculated t of 25,450 > t table 2.03951 was obtained, so it can be concluded that the poverty variabel (X) affects the crime variabel (Y).